Оптимізація періодичності часткового календарного технічного обслуговування системи послідовно-паралельної структури - Peschansky, A. I.; Prikhodko, R. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The mathematical model is constructed and the approximated values of reliability stationary characteristics of consistently-parallel system with partial calendar maintenance service of its consecutive part are found. Optimum terms of maintenance service realization are determined.